Mobile Dressing Trolleys Improve Satisfaction and Logistics on Pediatric Surgery Wards - Hannes Franck; Astrid Dempfle; Katja Reischig; Jonas Baastrup; Andreas Meinzer; Meike Kossakowski; Thomas Franz Krebs; Robert Bergholz (Children, 2023)
Background: Evidence-based data on the effect of dressing trolleys on children’s postoperative recovery are not available. The aim of this study was to evaluate a specific pediatric surgical dressing trolley on patient and caregiver satisfaction, as well as temporal and logistical aspects of the dressing change procedures. Methods: In a prospective observational non-randomized study, a total of 100 dressing changes were observed before (group 1) and after (group 2) the introduction of a pediatric surgical dressing trolley and the satisfaction, time and logistical factors were recorded on site. Results: The median preparation time, the duration of the dressing change and the total time decreased significantly from group 1 to group 2 by 1:11 min (p < 0.001); 1:56 min (p = 0.05) and 5:09 min (p = 0.001), respectively. The patient’s room was left significantly less often in group 2 to retrieve missing bandages. The median satisfaction of the medical staff increased by 12% in group 2 (p < 0.001). The satisfaction of the parents increased by 2.5% in group 2 (p = 0.042), and that of the nursing staff increased by 9.25% in group 2 (p = 0.015). Conclusions: Our results demonstrate the positive effects of a dressing trolley for pediatric surgical dressing changes by minimizing postoperative handling and manipulation of the child. It improves time and logistical factors as well as the satisfaction of those involved, which may lead to a faster recovery.